Evaluasi Layout Departemen Produksi PT ABC Menggunakan Analisis Kuantitatif Untuk Meminimasi Ongkos Material Handling - Fakhrina Fahma; Fatma Fitriana Sakinah (Performa: Media Ilmiah Teknik Industri, 2014)
PT ABC is a company enganged in the manufacture of drum oil, at first the company produces only one kind of drum namely non liquid leacker ( NLL).The high competition make pt abc add kind of product that is liquid leacker ( NLL) or drum with paint on the inside. So that companies must add some new machines resulting in the layout of a machine become commuting between from the building one into the building two. Research purposes this is designing layouts alternative to minimize cost material handling using methods quantitative analysis, that ' s using from to chart, outflow table, and priority scale table. After making the collection and processing data over distances total is 876,64 m. This distance longer 6.25 m compared with the layout of the beginning, namely 870,39 m. but the result of reckoning cost of materials handling produce a cost of RP 3.345.193,00 the cost is cheaper than the layout of the beginning, fund of RP 3.988.084,28